2019
DOI: 10.1016/j.landurbplan.2019.103666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of highways on bird distribution and soundscape diversity around Aldo Leopold’s shack in Baraboo, Wisconsin, USA

Abstract: In the 1940s, Aldo Leopold took extensive notes on birds and their sounds near his iconic shack in Baraboo, Wisconsin, USA. His observations, along with his land management techniques, helped frame his seminal book, A Sand County Almanac. After his death, two interstate highways were built near his property and subjected this historically significant area to traffic noise. While highways currently represent vital transportation corridors, their observed and potential impacts on biodiversity and ecosystem servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 86 publications
2
14
0
2
Order By: Relevance
“…This coincided strongly with the sound average, equivalent sound level (LeQ 30 ), produced by the highway over 30 minutes (Rashidi et al, 2019). Khanaposhtani et al (2019) observed increased richness and abundance of forest interior species with distance from two major highways in Canada. This was attributed partly to the intrusion of traffic noise pollution into the surrounding landscape (Khanaposhtani et al, 2019).…”
Section: Impacts On Richness and Abundancesupporting
confidence: 69%
See 1 more Smart Citation
“…This coincided strongly with the sound average, equivalent sound level (LeQ 30 ), produced by the highway over 30 minutes (Rashidi et al, 2019). Khanaposhtani et al (2019) observed increased richness and abundance of forest interior species with distance from two major highways in Canada. This was attributed partly to the intrusion of traffic noise pollution into the surrounding landscape (Khanaposhtani et al, 2019).…”
Section: Impacts On Richness and Abundancesupporting
confidence: 69%
“…Khanaposhtani et al (2019) observed increased richness and abundance of forest interior species with distance from two major highways in Canada. This was attributed partly to the intrusion of traffic noise pollution into the surrounding landscape (Khanaposhtani et al, 2019). Bird richness and abundance have also declined significantly through traffic noise playbacks in quiet (i.e., non-road) environments (McClure et al, 2013;Ware et al, 2015;Senzaki et al, 2020).…”
Section: Impacts On Richness and Abundancementioning
confidence: 82%
“…Canopy cover: Number of first returns above a height/total number of first returns [42]; Intensity sum of all non-ground points divided by intensity sum of all points [43]; Canopy gaps and ruggedness [44]; Fractional cover [45]; LiDAR penetration ratio (LPI), as the ratio between terrain points and total points [22].…”
Section: Cs: Canopy Covermentioning
confidence: 99%
“…Gini coefficient [48]; Simpson index [39]; Vertical gap index, measured as the total distance between individual canopy strata divided by maximum canopy height [43].…”
Section: Cs: Canopy Vertical Distributionmentioning
confidence: 99%
“…If the negative effects of anthropogenic noise have been thoroughly studied at the individual level through animal behavior and animal physiology studies (Slabbekoorn and Ripmeester 2008 ; Barber et al 2009 ; Brumm 2013 ; Shannon et al 2015 ), less research has been conducted at larger ecological scales. Anthropophony has been shown to be a prevalent part of preserved soundscapes (Francis et al 2011a , b ; Mullet et al 2015 ), and to have a role in the structure of soundscapes, in relation to massive noise generators, such as industrial sites (Duarte et al 2015 ; Deichmann et al 2017 ) or highways (Munro et al 2018 ; Khanaposhtani et al 2019 ). Anthropogenic noise can alter the benefits that humans may experience from natural soundscapes (Francis et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%